EGFR/EGFRvIII remodels the cytoskeleton via epigenetic silencing of AJAP1 in glioma cells. (10th September 2017) - Yang, Chao; Li, Yan-Sheng; Wang, Qi-Xue; Huang, Kai; Wei, Jian-Wei; Wang, Yun-Fei; Zhou, Jun-Hu; Yi, Kai-Kai; Zhang, Kai-Liang; Zhou, Bing-Cong; Liu, Cong; Zeng, Liang; et al.
Abstract: EGFR amplification and mutations are the most common oncogenic events in GBM. EGFR overexpression correlates with GBM invasion, but the underlying mechanisms are poorly understood. In a previous study, we showed that AJAP1 is involved in regulating F-actin to inhibit the invasive ability of GBM. In addition, in a GBM cell line, the AJAP1 promoter was highly bound by H3K27me3 and, through bioinformatics analysis, we found that AJAP1 expression was negatively correlated with EGFR. In this study, we found that the pathway downstream of EGFR had a higher activation level in GBM cell lines, which led to excessive tumor suppressor silencing. Therefore, we deduced that in glioma cells, the pathway downstream of EGFR remodels the cytoskeleton via AJAP1 epigenetic silencing to enhance invasion. Furthermore, MK2206 reversed AJAP1 downregulation by inhibiting the EGFR pathway. In vivo, MK2206 also inhibited the proliferation and local invasion of 87-EGFRvIII. These data suggest that activation of the EGFR signal transduction pathway genetically silences anti-oncogenes to enhance GBM malignancy. MK2206 might be a promising therapeutic for EGFR/EGFRvIII-positive GBMs. Highlights: AJAP1 expression was negatively correlated with EGFR using a bioinformatics analysis. Activation of the EGFR signal transduction pathway inhibits AJAP1 expression through a PI3K/Akt-mediated, EZH2-dependent pathway. Activating EGFR downstream pathway remodels the actin (F-actin) cytoskeleton in vitro or glioblastoma models. Targeting AKT by Mk2206 might be an effective approach for glioblastomas with EGFRvIII.